Resolving the technology–performance paradox: A capability–technology–performance model of SME digital transformation - Fang, Zhang; Hattakitpanitchakul, Wanlapa; Khunthong, Ubonwan (Edelweiss Applied Science and Technology, 2025)
In the rapidly evolving digital economy, digital transformation has become critical for small and medium-sized manufacturing enterprises (SMEs) seeking to sustain competitiveness. Yet, technology investment alone does not guarantee performance gains, and the interplay between organizational capabilities and technology application remains underexplored. This study investigates how learning capability and channel integration capability shape the application of digital technologies and, in turn, organizational performance. Using survey data from 476 SMEs in Kunming, China, we construct and empirically validate a structural equation model grounded in the resource-based view and organizational learning theory. The findings show that both capabilities exert significant direct effects on performance and also enhance it indirectly via digital technology application. Importantly, technology application plays a partial mediating role, indicating that internal capabilities not only drive outcomes directly but also magnify the value of digital tools. This research advances digital transformation theory by articulating a “capability–technology–performance” pathway and integrating resource-based and organizational learning perspectives. Practically, it offers SME managers a dual-path framework to convert digital investments into measurable results and provides insights for policy support in capability development.